HAKIM KOMISARIS (APRESIASI TERHADAP RKUHAP) - Noor Ichwan Ichlas Ria Adha (Jurnal Hukum dan Peradilan, 2015)
Inside RKUHAP contain new institution, that is commissioner judge, regarding the commissioner judge to be diversification opinion, that is to be must the commissioner judge as consequences ratification ICCPR convention. And then to be needn’t because of competence the commissioner judge to be done deep institution prior to judicature. Nevertheless when we see interest victims not yet including with fine on the KUHAP and the KUHP, writer to see inside RKUHAP necessary to be need interest victims and interest community take place criminal act. After inspect criminal procedure law inside Islam and adat recht, writer contemplate necessary to be commissioner judge inside the RKUHAP with of competence to bridge interest victims, interest community society and interest offender.Keywords: Judge, Commissioner, Criminal Procedure Code Bill